(untitled) (Bangladesh Journal of Otorhinolaryngology, 2022)
Objective: To examine the efficacy of combined use of intranasal steroids, antibiotics and monteleukast for improving adenotonsillar hypertrophy. Materials and Methods: This prospective study was done at Bangladesh ENT Hospital, Dhaka from January 2020 to June 2021. 50 children were included with primary symptoms of mouth breathing, snoring and sleep disturbances. X-ray soft tissue nasopharynx lateral view was done before and after treatment for comparison. All were prescribed intranasal fluticasone, phenoxymethyl penicillin and monteleukast for 3 months and followed up after completion of 3 months treatment. Results: The age of the children ranged from 2-12 years with mean age 5.4 years. There were 30 female and 20 male with female male ratio 3:2. 30 patients (60%) got complete relief of primary symptoms, 12patients (24%) got moderate improvement of symptoms and 8(16%) patients got no benefit of medical treatment and referred for surgery. Conclusion: Intranasal steroid along with oral penicillin and monteleukast are effective reducing size of adenotonsillar hypertrophy, relieving symptoms and reducing the need for surgery. Bangladesh J Otorhinolaryngol 2022; 28(1): 16-21